Realizações dos sufixos -(z)inho /-(z)im no português brasileiro dialetal: análise variacionista - Geralda Fátima de Souza Rodrigues (2015)
The purpose of this work is to study diminutive suffixes in Brazilian Portuguese and determine whether this phenomenon is an indicator of different Brazilian dialects. Internet sites and dictionaries indicate the use of diminutives as one of the specificities of this mineirês dialect. These references help identify the use of diminutives as stereotypes. This research is part of a larger project, entitled A construção de um dialeto: a língua portuguesa em Minas; which general objective is to scientifically analyze linguistic phenomena typical of the Mineiro dialect. Thus, the purpose of this research is to conduct a sociolinguistic study of the diminutive suffixes in two different cities in Minas Gerais: Mariana and Piranga, with the variants:-inho/ -im, -zinho/-zim. Therefore, the general objectives are to explain the origin of these variants, conditions of use, and provide a sociolinguistic analysis of the forms (z)inho,-(z)im by describing their distribution, origin, socio-economic and linguistic status. The specific objectives are: a) verify the frequency and distribution of variants of a representative sample in the cities of Mariana and Piranga; b) compare the two dialects from the two cities, using the variants in question; c) assess the strength of internal and external factors; d) explain the results achieved in light of socio-historical information, and finally, e) determine whether this change is an ongoing process. The suggested hypothesis is that the change in question is diatopical by nature. As theoretical and methodological support, we use the assumptions of the Theory of Variation and Linguistic Changes (Labov, 1972a, b, 1974, 1994, 2001, 2008, 2010), Hewstone & Giles (1997). Statistical analysis is conducted through the use of the Goldvarb X program.